Optimization of Kalimasada Program Through "Klampid New Generation" Application in Surabaya City - Ahmad Luthfi; Ilham Nur Hanifan; Naufal Ludya Mashur; Fifiandina Yudha (Kolaborasi : Jurnal Administrasi Publik, 2023)
Focus of population administration services by the Surabaya City Population and Civil Registration Office changed from traditional to electronic through the Klampid New Generation application. This study primarily aims to evaluate the effectiveness of the Kalimasada program, which is facilitated through the Klampid New Generation application in Surabaya City. The research approach utilized is descriptive and qualitative in nature, utilizing primary data obtained through in-depth interviews and observations. Additionally, secondary data from relevant government websites and other resources related to the research theme are incorporated. Valuable insights are further derived from extensive interviews conducted with key stakeholders. The study's findings reveal that a considerable portion of the population lacks familiarity with the operational aspects of the Klampid New Generation Application. As a result, there is a notable requirement for increased efforts by the government to raise awareness through extensive public campaigns. However, in terms of implementation, the Kalimasada program emerges as a highly effective tool, contributing significantly to the promotion of civic awareness regarding the organized management of population administration within Surabaya's dynamic urban environment.